Do large thyroid nodules (≥4 cm) without suspicious cytology need surgery? - Kang, Seokmin; Kim, Eunjin; Lee, Sunmin; Kim, Jin Kyong; Lee, Cho Rok; Kang, Sang-Wook; Lee, Jandee; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn (Frontiers in Endocrinology, 2023)
Background: Fine-needle aspiration biopsy (FNAB) is a good diagnostic tool for thyroid nodules; however, its high false-negative rate for giant nodules remains controversial. Many clinicians rec-ommend surgical resection for nodules >4 cm owing to an increased risk of malignancy and an in-creased false-negative rate. This study aimed to examine the feasibility of this approach and inves-tigate the incidence of malignancy in thyroid nodules >4 cm without suspicious cytology based on medical records in our center. Methods: This was a retrospective analysis of 453 patients that un-derwent preoperative FNAB for nodules measuring >4 cm between January 2017 and August 2022 at Severance Hospital, Seoul. Results: Among the 453 patients, 140 nodules were benign and 119 were indeterminate. Among 259 patients, the final pathology results were divided into benign (149) and cancerous (110) groups, and the prevalence of malignancy was 38.9% in the benign group and 55.5% in the indeterminate group. Among the malignancies, follicular carcinoma and follicular variants of papillary carcinoma were observed in 83% of the cytologically benign group and 62.8% of the in-determinate group. Conclusions: Preoperative FNAB had high false-negative rates and low diag-nostic accuracy in patients with thyroid nodules >4 cm without suspicious cytologic features; therefore, diagnostic surgery may be considered a treatment option.